A mathematical model to evaluate the polymer flooding performances - Afshin Davarpanah; Behnam Mirshekari (Energy Reports, 2019)
Due to the enormous demand for crude oil, the selection of appropriate and economical techniques to enhance the oil recovery are always considered as the major concerns in reservoir developments. Polymer flooding is considered as one of the chemical enhanced oil recovery techniques especially for heavy oil reservoirs by the sweep efficiency improvement. The objective of this study is to perform a mathematical model to evaluate the polymer flooding performances in the presence of saturation profile and cross flow effect to validate the accuracy of the model with simulated field data. Thereby, the results of this developed model indicate that the model is approximately matched with the simulated field data rather than previous models. Furthermore, some geological problems such as high permeable channeling and semi-sealing issues are considered in the model to calculate the pressure integral and how each parameter would change regarding the cumulative pore volume alteration. Consequently, the proposed model would be an appropriate choice to verify the pressure integral which is compared with the simulated field data by the consideration of saturation distribution and cross flow effect.
Keywords: 330; Polymer flooding; Mathematical model; Saturation profile; Cross flow effect; Geological problems